DECADES OF RURAL TOURISM DEVELOPMENT IN HUNGARY: At the border of old and new rural tourism? - Kovács, Dezső (Turisztikai és Vidékfejlesztési Tanulmányok, 2021)
Rural tourism as a rural economic and social phenomenon, is increasingly sensitive to changes in the world and within the country. Its development and history can be connected to the great world economic crises and the political system change and policy changes within the country. During the past thirty years rural tourism has flourished, declined, revived in new forms with new actors and attracted and is attracting new customers. A generational shift has taken place, and the main goal of the activities is not just to obtain additional income but to build an enterprise for profit. The former rural tourism host families no longer enjoy positive discrimination; the countryside has become a neutral investment territory. Behind these phenomena are new values and tastes and new interests and fashions. Due to the COVID-19 world crisis, those places in the countryside where rural tourism supply is present are being revalorized. Although this study is based on a survey from 2012, the events since then show that it is time to reevaluate and reconsider everything that we learned and thought about rural tourism and rural hospitality in the past.